Nannoconid assemblages from the upper jurassic and lower cretaceous sediments of the Vaca Muerta and agrio formations (Neuquén Basin, Argentina) - Lescano, Marina Aurora (2014)
Several studies on calcareous nannofossils have been performed through the last years in Argentina, with the aim of establishing geologic correlations between different stratigraphic sections of the Neuquén Basin and with other Mesozoic Tethyan basins. The nannoconids, considered of uncertain affinity, have been included within the calcareous nannofossils, because of their calcareous algal origin, size and morphological features. The gender Nannoconus has appeared on the Early Tithonian and has extinguished in the Campanian. In the Neuquén Basin the late Tithonian-Hauterivian interval is represented in sediments of the Vaca Muerta and Agrio Formations. In this contribution Late Jurassic- Early Cretaceous nannoconid assemblages recognized in thirteen sections of the Neuquén Basin are disclosed. Sections are: Arroyo Durazno (35°05?S-69°45?W), Las Loicas (35°47?S-70°09?W), Don Alfaro (36°18?S-70°21?W), Lonco Vaca (36°22?S-70°12?W), Quebrada Maravilla (36°28?S-70°12?W), Cerro La Parva (37°16?S-70°26?W), Mina San Eduardo (37°31?S-70°01?W), Loma Rayoso (37°36?S-70°01?W), Agua de la Mula (38°04´S-70°01?W), Bajada del Agrio (38°27S-70°04W), Cerro Birrete (39°17?S-70°0.5´W), Barda Cerro Marucho (39°26?S-70°13´W) and Cerro Marucho (39°26?S-70°13W). The nannoconids have been found in all studied sections, and therefore have a wide geographic distribution in the analyzed formations, and are represented by 7 species and 11 subspecies of Nannoconus. The finding of Nannoconus elongatus minutus, Nannoconus quadriangulus apertus, Nannoconus steinmannii minor, Nannoconus truitti frequens, Nannoconus truitti rectangularis and N. wintereri in the basin, constitute their first references for Argentina, and for two of them they are the first records for the Southern Hemisphere. In sediments of the Vaca Muerta Formation the first occurrence (FO) of N. wintereri (Tithonian) has been identified as well as the FOs of N. kamptneri minor, N. kamptneri kamptneri, N. steinmannii minor and N steinmannii steinmannii (Berriasian). These bioevents indicate the calcareous nannofossil Biozones NJK-NK1. In addition, three calcareous nannofossil bioevents have been recognized in sediments of the Agrio Formation, and include the FO of N. bucheri and N. circularis assigned to the late Valanginian, and the FO of N. ligius correlated with the late Hauterivian. All these bioevents in the Neuquén Basin belong to the CC4A-CC4B Zone. Taking this study into account, Nannoconus minutus elongatus, Nannoconus quadriangulus quadriangulus, Nannoconus quadricanalis, Nannoconus truitti frequens and Nannoconus truitti rectangularis would extend their known stratigraphic ranges. During the Late Jurassic and Early Cretaceous, the nannoconid assemblages suggest Tethyan affinities and they would allow us to establish reliable intercontinental correlations between the Neuquén Basin and the Mediterranean Region.